2014
DOI: 10.1016/j.bbrc.2014.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomics of chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a complex disease with both environmental and genetic determinants, the most important of which is cigarette smoking. There is marked heterogeneity in the development of COPD among persons with similar cigarette smoking histories, which is likely partially explained by genetic variation. Genomic approaches such as genomewide association studies and gene expression studies have been used to discover genes and molecular pathways involved in COPD pathogenesis; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 121 publications
(133 reference statements)
1
38
1
Order By: Relevance
“…While certain processes were most enriched in specific disease subtypes, there was also notable overlap in processes across subtypes. Compared to previous blood expression studies in smokers with and without COPD, the role of inflammatory responses is consistent with previous findings [11]. Prior histologic studies of lung tissue from smokers with COPD demonstrate increased presence of multiple inflammatory cell sub-populations in emphysematous lungs [17,18] and various aspects of the role of innate and adaptive immunity in response to cigarette smoke have been demonstrated by multiple groups [19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While certain processes were most enriched in specific disease subtypes, there was also notable overlap in processes across subtypes. Compared to previous blood expression studies in smokers with and without COPD, the role of inflammatory responses is consistent with previous findings [11]. Prior histologic studies of lung tissue from smokers with COPD demonstrate increased presence of multiple inflammatory cell sub-populations in emphysematous lungs [17,18] and various aspects of the role of innate and adaptive immunity in response to cigarette smoke have been demonstrated by multiple groups [19].…”
Section: Discussionsupporting
confidence: 88%
“…While COPD is defined by a ratio of <0.7 between the forced expiratory volume in 1 s/forced vital capacity (FEV 1 /FVC ratio), the smoke-induced lung damage characteristic of COPD occurs across the full spectrum of smokers, including those who do not meet the spirometric criteria for COPD [9,10]. Gene expression studies in COPD have been recently reviewed, and while there is notable heterogeneity between studies, most studies in lung tissue and peripheral blood have identified enrichment of differentially expressed genes in inflammatory pathways related to immune regulation, specifically B-cell and T-cell development and differentiation [1113]. …”
Section: Introductionmentioning
confidence: 99%
“…1 Multiple lines of evidence have suggested that a wide range of factors such as genetic susceptibility and environment are involved in the initiation and progression of COPD. 7,8 Among all these biomarkers, microRNAs (miRNAs) have emerged to be key biomarkers for the prognosis and diagnosis of patients with COPD. Previous studies demonstrated that various biomarkers and molecular pathways are involved in the pathogenesis of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications, such as histone modification, have been reported in COPD in several studies . For example, histone deacetylase (HDAC) activity has been reported to be decreased in alveolar macrophages in COPD .…”
Section: Discussionmentioning
confidence: 99%